2014
DOI: 10.1103/physrevb.89.195206
|View full text |Cite
|
Sign up to set email alerts
|

Elemental tellurium as a chiralp-type thermoelectric material

Abstract: The thermoelectric transport properties of elemental tellurium are investigated by density functional theory combined with the Boltzmann transport equation in the rigid band approximation. We find that the thermoelectric transport properties parallel and perpendicular to the helical chains are highly asymmetric (almost symmetric) for p-(n-) type doped tellurium due to the anisotropic (isotropic) hole (electron) pockets of the Fermi surface. The electronic band structure shows that the lone-pair derived uppermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(134 citation statements)
references
References 36 publications
(51 reference statements)
5
128
0
1
Order By: Relevance
“…Bulk Te forms a degenerate semiconductor with a narrow bandgap of 0.33 eV, in which the Fermi level is positioned close to the valence band. [ 27 ] The work function of the TeNWs is assumed to be the same as that of bulk Te. [ 28 ] The work functions of PEDOT:PSS and rGO were measured using ultraviolet photoelectron spectroscopy (UPS), Figure S11).…”
Section: Carrier Transport Characteristics Of Gdte Papermentioning
confidence: 99%
“…Bulk Te forms a degenerate semiconductor with a narrow bandgap of 0.33 eV, in which the Fermi level is positioned close to the valence band. [ 27 ] The work function of the TeNWs is assumed to be the same as that of bulk Te. [ 28 ] The work functions of PEDOT:PSS and rGO were measured using ultraviolet photoelectron spectroscopy (UPS), Figure S11).…”
Section: Carrier Transport Characteristics Of Gdte Papermentioning
confidence: 99%
“…1a,b. To the best of our knowledge, the band structure of tellurium has been established before the 1970s by theoretical [20][21][22][23][24][25] and experimental 18,26,27 studies, which identified a gap size of 0.32 eV 18,19 and the valence band maxima (VBM) located slightly off the H-and H'-point (Fig. 1f).…”
mentioning
confidence: 99%
“…Another qualitative change that occurs in a number of 2D materials is the inversion of the parabolic dispersion at a band extremum into a 'Mexican hat' dispersion. [2][3][4] Mexican hat dispersions are also referred to as a Lifshiftz transition 3,5,6 , an electronic topological transition 7 or a camel-back dispersion 8,9 .…”
Section: Introductionmentioning
confidence: 99%